Peltigera serusiauxii ( Lecanoromycetes , Ascomycota ), a new species from Papua New Guinea and Malaysia - Nicolas Magain; Bernard Goffinet; Antoine Simon; Jaya Seelan Sathiya Seelan; Ian Daniel Medeiros; François Lutzoni; Jolanta Miadlikowska (Plant and Fungal Systematics, 2020)
Peltigera serusiauxii is proposed here as a new species from Papua New Guinea and Sabah, northern Borneo (Malaysia). The species belongs to the polydactyloid clade of section Polydactylon . Because of its large thalli with a glabrous upper surface, this species was previously identified as P. dolichorhiza , but it differs by its polydactylon-type lower surface and the high amount of dolichorrhizin. It appears to be a strict specialist in its association with Nostoc phylogroup IX throughout its known distribution. This is one of many undescribed species remaining to be formally described within the genus Peltigera , especially in Asia and Australasia.